KEPEMIMPINAN KEKELUARGAAN DAN EFISIENSI DI SEKOLAH QUR’AN INDONESIA - Rakhmad Agung; Triyani; Ridwan Maulana Saputra; Bilal Al Aday (JIP: Jurnal Ilmu Pendidikan, 2026)
Leadership plays an important role in sustaining non formal educational institutions. This study examines family based leadership and management efficiency practiced by the founder of Sekolah Qu’ran Indonesia in Plupuh, Sragen. The research focuses on leadership patterns that shape the working atmosphere and institutional management. This study employs a descriptive qualitative approach. Data were collected through in depth interviews with the founder and participatory observation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing.The findings indicate that leadership at Sekolah Qu’ran Indonesia is participatory and family oriented. Teachers are positioned as part of an institutional family and involved in decision making through deliberation, routine evaluation, and pre teaching briefings. This approach creates a supportive working atmosphere and strengthens collective responsibility. Management efficiency is reflected in the optimal use of limited resources. The study shows that family based leadership and efficiency support institutional continuity